CATHEPSIN G AND NEUTROPHIL ELASTASE INCREASE EXPRESSION OF MHC I ON THE CELL SURFACE OF DIFFERENT CELL LINES - Allayarova, Maiya (Nazarbayev University School of Sciences and Humanities, 2025)
Major histocompatibility complex class I (MHC I) molecules are essential structures that enable the immune system to identify and destroy abnormal cells by presenting intracellular antigens on the cell surface. Infected or cancerous cells often escape immune recognition by downregulating MHC I molecules. Neutrophil-derived serine proteases, such as cathepsin G (CatG) and neutrophil elastase (NE), can influence MHC I expression in different cells, including peripheral blood mononuclear cells (PBMCs), glioblastoma cells, and breast cancer cells. This study examined such modulation by CatG and NE in lung cancer cell lines (A549 and H1299) and immune cells (Jurkat, T cell line). Flow cytometry analysis demonstrated that NE significantly upregulated MHC I expression in all cell types tested. In contrast, the impact of CatG was significantly more pronounced solely in Jurkat cells, implying that these cells may exhibit a more adept antigen presentation system. The apoptosis array confirmed that the observed changes in MHC I levels occur independently of cell death processes. Moreover, colorimetric substrate assay experiments showed that serum components inhibited CatG activity, suggesting that endogenous protease inhibitors may modulate its impact on antigen presentation. Together, these findings provide insights into the distinct roles of CatG and NE in increasing MHC I cell surface expression and offer potential ideas for developing therapeutic strategies aimed to improve immune recognition by generating small molecules which enhance the catalytic activity of CatG and NE.
Keywords: MHC I; Cathepsin G; Neutrophil elastase; type of access: open access